A DECADE OF SCIENCE EDUCATION RESEARCH IN INDONESIA: TRENDS, LEARNING MODELS, AND STUDENT OUTCOMES - Teguh Febri Sudarma; Rara Amanda; Mayfa Dwi Arvi; Kezia Elmaesia Tarigan; Indah Maysaroh Siagian (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to identify the most frequently examined learning models in science education research in Indonesia, map the most commonly studied learning outcomes, and analyze the patterns of relationships between the two.Methodology – This study employs an SLR  design following the PRISMA 2020 guidelines. Data retrieval was conducted via the Scopus database using the Publish or Perish application, covering the timeframe 2016–2025. Of the total 509 identified articles, 57 empirical studies were selected based on strict inclusion criteria. Data were analyzed using thematic synthesis to map the frequencies of models and outcomes, and to identify emerging patterns of relationships.Findings –The results indicate that IBL is the most frequently studied model (28 studies), followed by PBL and PjBL. The most commonly examined outcomes are critical thinking skills (21%), science process skills (17.5%), and academic learning outcomes. Relationship patterns fall into three configurations: one-to-many, many-to-one, and exclusive. Trends for 2024–2025 indicate a shift toward more holistic outcomes such as computational thinking, teachers’ pedagogical competencies, and reflective skills. This shift can be linked to the dynamics of the Merdeka Curriculum, the strengthening of project-based learning, and the demands of 21st-century competencies.Contribution – The dominance of the IBL model and the focus on critical thinking skills as learning outcomes reflect methodological convenience and alignment with curriculum policy rather than pedagogical superiority alone, with significant gaps remaining in non-dominant models (Cooperative Learning, Discovery Learning, ADDIE, Susan Loucks-Horsley) and non-cognitive learning outcomes. This study contributes theoretically through a relational model–outcome mapping framework that reveals one-to-many, many-to-one, and exclusive patterns, and practically by providing a basis for educators to select learning models and a roadmap for future research agendas.